Solar Concentrators and Solar-pumped Lasers - Garcia, Dário Machado (2023)
Innovative substitutions for Fresnel lenses concentrators by Elliptical shaped Fresnel lens (ESFL) and parabolic concentrators by ring array concentrator (RAC) models are presented, as well as, advances of solar-pumped lasers of Ce:Nd:YAG operation during a clean and clouded weather. The design of the ESFL and RAC were modelled into Zemax® non-sequential ray-tracing soft-ware from well-defined mathematical equations. Most of the key parameters were analysed and the resulting outputs were compared and documented in publications. The design parameters for solar-pumped lasers were optimized using Zemax®, and then the LAS-CAD™ laser cavity system software was used to further optimize the laser resonator parameters. A solar laser prototype was built with an active medium of Ce:Nd:YAG and tested using a heliostat-parabolic mirror system at both NOVA University of Lisbon and Procédés, Matériaux et Énergie Solaire - Centre National de la Recherche Scientifique (PROMES-CNRS) in Odeillo-Font Romeu, France. The ESFL offers a 4.58 W/mm2 increase in solar flux concentration compared to a Fresnel lens, which only achieves 2.66 W/mm2 at the same size and focal distance. A 3.14 m2 RAC with a focal length of 300 mm can capture over 18 W/m2. The first recorded Ce:Nd:YAG solar laser operating with a small collection area of 0.293 m2 at the NOVA facility, produced a multimode output power of 11.2 W, resulting in a solar-to-laser power conversion efficiency of 3.37%, with a minimum threshold pump power of 66 W. The MSSF parabolic mirror from PROMES-CNRS achieved a lower threshold pump power of 32.4 W using a smaller col-lection area of 0.075 m2, and during cloudy weather, a threshold pump power was further reduced to 29.2 W. Furthermore, cloud interference improved the solar-to-laser conversion efficiency to 6.32%, nearly tripling the 2.32% efficiency on a clear sky, while the solar laser conversion efficiency of 21.47 W/m2 was nearly twice the value of 12.62 W/m2 on a clear sky. The research efforts performed during this work are explained. Experimental results are dis-cussed, and future suggestions are proposed.